2009
DOI: 10.1162/artl.2009.15.2.15204
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Learning on Evolution: A Mathematical Framework

Abstract: The Baldwin effect can be observed if phenotypic learning influences the evolutionary fitness of individuals, which can in turn accelerate or decelerate evolutionary change. Evidence for both learning-induced acceleration and deceleration can be found in the literature. Although the results for both outcomes were supported by specific mathematical or simulation models, no general predictions have been achieved so far. Here we propose a general framework to predict whether evolution benefits from learning or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In the last two decades, a few studies to enhance the understandings of Baldwinian MAs (26)(27)(28)(29) have been reported. However, to the best of our knowledge little progress on study of Lamarckian MA in non-linear programming has been made so far (30)(31)(32) with few exceptions (33).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, a few studies to enhance the understandings of Baldwinian MAs (26)(27)(28)(29) have been reported. However, to the best of our knowledge little progress on study of Lamarckian MA in non-linear programming has been made so far (30)(31)(32) with few exceptions (33).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of the adaptability driver has been repeatedly modelled, both analytically (Ancel, , ; Mills & Watson, ; Borenstein, Meilijson & Ruppin, ; Borenstein, Feldman & Aoki, ; Paenke, Kawecki & Sendhoff, ) and by simulation (Hinton & Nowlan, ; Nolfi, Parisi & Elman, ; Suzuki & Arita, ; Red'ko, Mosalov & Prokhorov, ). The outcome of this theoretical activity has been variable, sometimes supporting the adaptability driver hypothesis and sometimes not.…”
Section: The Adaptability Drivermentioning
confidence: 99%
“…Paenke et al . () proposed a general framework that explained both effects. Spontaneously expressing a behaviour that had been learned in previous generations could be costly if it meant that the animal lost all of its ability to learn.…”
Section: The Adaptability Drivermentioning
confidence: 99%
See 1 more Smart Citation
“…The guiding effect of Baldwinian learning in the search was first verified by Hinton and Nowlan [8]. In the following years researches were taken on the characteristics in the process of Baldwinian evolution [23,15,22,14], the interaction of learning, evolution and development [4,5,6], and the fact that Baldwinian learning can also be hiding [20,21]. Furthermore there are works trying to combine Baldwinian and Lamarckian evolution [3,9,2].…”
Section: Introductionmentioning
confidence: 99%